Characteristics and antioxidant activity of Maillard reaction products from β-lactoglobulin and isomaltooligosaccharide - Wang, Qingyu; Li, Jiayang; Tu, Yaqi; Cai, Jianping; Ren, Fazheng; Zhang, Hao (Frontiers in Nutrition, 2023)
Starch-derived isomaltooligosaccharide (IMO) is potentially used as prebiotics in infant formulas. Given that they are non-digestible carbohydrates rich in reducing substrates, it's crucial to understand if they can interact with β-lactoglobulin (β-LG) to produce Maillard reaction products (MRPs) and how these MRPs might influence the nutritional properties of β-LG. In our investigation, we conjugated β-LG with IMO to generate MRPs. Using a spectrophotometer, we identified the intermediates and assessed browning. We also evaluated changes in free amino groups and structural alterations. The antioxidative activity of the resulting compounds was assessed using DPPH and the ferric reducing/antioxidant power (FRAP) assay. Our data revealed increased visible absorption and fluorescence intensity, suggesting the formation of intermediate and browning products. The content of free amino groups diminished by 33%, supporting the conjugation of IMO with β-LG. However, circular dichroism results indicated no significant alterations in the secondary structure of β-LG.Notably, the β-LG-IMO MRPs exhibited enhanced 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicalscavenging activity and ferric reducing/antioxidant power (FRAP). The findings provide insights into the characteristics and antioxidant activities of the conjugates derived from IMO and dairy protein in infant formula.